1999
DOI: 10.1159/000029896
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Constituents of Moisturizers: Water-Binding Properties of Urea and NaCl in Aqueous Solutions

Abstract: A water content of about 10% in the horny layer is necessary for softness and pliability of this part of the epidermis. In conditions with dry skin, emollients of different types are used. It is important that solid data are collected about the effect of the ingredients of emollients and moisturizers. Urea has since long been used in the treatment of dry skin. In the present report, the mixture of urea and sodium chloride has been analyzed with respect to its effect on the water vapor pressure in concentrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Major factors accounting for this effect might be first hydration of the stratum corneum by increasing the water binding (urea) and second by absorbing and retaining moisture (hygroscopicity, NaCl). This accords well with the findings of Miettinen et al [5], who reported that the reduction in water vapour pressure by sodium chloride and urea was additive. On the basis of chemical studies of an aqueous solution, Miettinen et al [5] suggested that either sodium chloride or urea is effective in mixtures, but the effect is greater when they are used together.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Major factors accounting for this effect might be first hydration of the stratum corneum by increasing the water binding (urea) and second by absorbing and retaining moisture (hygroscopicity, NaCl). This accords well with the findings of Miettinen et al [5], who reported that the reduction in water vapour pressure by sodium chloride and urea was additive. On the basis of chemical studies of an aqueous solution, Miettinen et al [5] suggested that either sodium chloride or urea is effective in mixtures, but the effect is greater when they are used together.…”
Section: Discussionsupporting
confidence: 93%
“…Later improvements in moisturisers were made by Hagströmer/Nyrén/Emtestam adding active substances, such as urea, lactic acid and sodium chloride [3,4]. Recently, Miettinen et al [5], after analysing water vapour pressure reduction in vitro, have suggested that by adding NaCl and urea to a moisturiser, the combination might be more effective in this mixture than one of them alone. For a recent review on moisturisers, the chemistry and effects, please see Lodén and Maibach [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble hygroscopic substances in the natural moisturising factor cause hygroscopicity of the SC -i.e., the ability to absorb water [5]. Urea increases the waterholding capacity of the SC because it binds water [6]. Several clinical studies have indicated that moisturisers containing urea are useful for the treatment of dry or eczematous skin in atopic patients [1,7,10] and of hyperkeratotic skin [8,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Miettinen et al [6] suggested, on the basis of a reduction in water pressure in vitro, that urea and sodium chloride in aqueous solution have additive effects. Therefore, it was natural to start a clinical study to estimate the effect of a new combined moisturiser in such patients.…”
Section: Introductionmentioning
confidence: 99%